White lighting: A provisional model for predicting perceived tint in "white" illumination. Issue 5 (9th December 2013) - Rea, M. S.; Freyssinier, J. P.
Abstract Recently, a line of minimum tint in chromaticity space for sources of illumination of different correlated color temperatures (CCTs) from 2700 K to 6500 K has been reported. This line of minimum tint did not correspond to the line of blackbody radiation implicitly associated with sources of white illumination used in architectural applications. It was noted that chromaticities along the line of minimum tint were not metamers but, rather, should represent, for a given CCT, chromaticities where the neural signals from the two spectral opponent channels were minimized. Earlier work provided a theoretical framework for representing the four unique hues where the neural signals from one spectral opponent channel are minimized. This framework was used here to quantitatively represent the line of minimum tint and then to empirically test whether this representation could predict the amount of tint perceived in six different sources of "white" Illumination." Based on these results, a provisional model is proposed for describing the tint and the amount of tint perceived in "white" Illumination used in architectural applications. © 2013 Wiley Periodicals, Inc. Col Res Appl, 39, 466–479, 2014